Poems masquerading as treatment refractory cidp: a case series. Issue 5 (8th May 2017) - Nham, Benjamin; Brown, Christina; Khoo, Lianne; Gibson, John; Spies, Judith; Jankelowitz, Stacey
Abstract : Objectives: Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes syndrome (POEMS) is a rare multi-system disease that occurs in the setting of a monoclonal plasma cell dyscrasia. The polyneuropathy component can often mimic CIDP. Criteria for the diagnosis of POEMS have been recently updated and the presence of an elevated serum vascular endothelial growth-factor (VEGF) level is now a major diagnostic criterion. Haematological series suggest a 50% or less response to bone marrow transplant in POEMS. We describe the rapid neurological recovery in three POEMS patients who had disabling neuropathy as the prominent part of their presentation and underwent bone marrow transplant. Cases: A 58 years old woman with essential thrombocytosis, IgA lambda paraproteinemia and CIDP that was refactory to both IVIG and regular plasma exchange; a 52 years old man with IgG lambda paraproteinemia, peripheral oedema and worsening CIDP despite fortnightly IVIG; and a 54 years old woman with demyelinating neuropathy, hepatomegaly, plasmacytomas and trace lambda light chains, were all shown to have raised VEGF levels. They were referred for bone marrow transplant on confirmation of the diagnosis of POEMS as they were rapidly becoming unable to mobilise independently despite treatment of their CIDP. All three patients were treated with autologous stem cell transplant with both clinical and neurophysiological improvement over months. The functional improvements in each case were: 1) wheelchair and near bedbound to walking without aids in 12 months 2) wheelchair and bedbound to walking independently with a pick-up frame in 6 months and 3) walking with a frame to unaided mobility within 3 months. Conclusions: POEMS is rare difficult to diagnose but treatable condition that can mimic CIDP. Serum VEGF level is an important criterion to consider in diagnosis. Neurological recovery is fairly rapid and, in our experience, more promising than that quoted in the haematalogical literature.